Long-Unidirectional Palm and Sisal Fibers Reinforced Composite: An Experimental Investigation - Sebti Jaballi; Imed Miraoui; Hedi Hassis (Journal of Natural Fibers, 2017)
This paper focuses mainly on investigating the mechanical properties of mortar reinforced with long-unidirectional vegetable fibers such as palm fibers and sisal fibers. The mechanical properties of fibers are also studied by considering fiber tensile test and fiber coupling test to analyze the twist-extension coupling and the tensile strength. Fibers were manually extracted from palm and sisal leaves. Laminated mortar specimens with fibers volume fraction ranging between 0% and 1.95% were prepared. The long unidirectional oriented fibers were placed on the lower part of the mortar. The influence of curing conditions on flexural strength of laminated mortar specimens was analyzed by considering two curing conditions: WCCC (wet chamber curing condition) and LCC (laboratory curing condition). Results confirm that the optimum fiber volume fraction was evaluated as 1.4% for Palm fiber-reinforced mortar. Better mechanical performance was accorded to the Palm fiber reinforced mortar in WCCC case due to the availability of water which is necessary to cement hydratation. Long Sisal fiber submitted to a tensile load shows coupling phenomenon between twist and extension which has a mechanical effect on the matrix behavior.